Cortisol levels and suicidal behavior: A meta-analysis. (January 2016) - O'Connor, Daryl B.; Ferguson, Eamonn; Green, Jessica A.; O'Carroll, Ronan E.; O'Connor, Rory C.
Highlights: The results show that age moderates the association between naturally occurring cortisol levels and suicide attempts. The association between cortisol and suicidal attempt reverses when the mean age of the sample is 40 years or older. We feel these findings are exciting, novel and have potential implications for theory and intervention. Abstract: Suicide is a major cause of death worldwide, responsible for 1.5% of all mortality. The causes of suicidal behavior are not fully understood. Dysregulated hypothalamic–pituitary–adrenal (HPA) axis activity, as measured by cortisol levels, is one potential risk factor. This meta-analytic review aimed (i) to estimate the strength and variability of the association between naturally fluctuating cortisol levels and suicidal behavior and (ii) to identify moderators of this relationship. A systematic literature search identified 27 studies ( N = 2226; 779 suicide attempters and 1447 non-attempters) that met the study eligibility criteria from a total of 417 unique records initially examined. Estimates of effect sizes ( r ) obtained from these studies were analysed using Comprehensive Meta-Analysis. In these analyses, we compared participants identified as having a past history of suicide attempt(s) to those with no such history. Study quality, mean age of sample and percentage of male participants were examined as potential moderators. Overall, there was no significant effect of suicide group on cortisol. However, significant associations between cortisol and suicide attempts were observed as a function of age. In studies where the mean age of the sample was below 40 years the association was positive (i.e., higher cortisol was associated with suicide attempts; r = .234, p < .001), and where the mean age was 40 or above the association was negative (i.e., lower cortisol was associated with suicide attempts; r = −.129, p < .001). These findings confirm that HPA axis activity, as indicated by age-dependent variations in cortisol levels, is associated with suicidal behavior. The challenge for theory and clinical practice is to explain the complete reversal of the association with age and to identify its clinical implications.